The House on Henry Street : The Enduring Life of a Lower East Side Settlement - Snyder-Grenier, Ellen M. (Ellen Marie) (Book collections on Project MUSE., 2020)
"Through personal narratives, vivid images, and previously untold stories, Ellen M. Snyder-Grenier chronicles Henry Street's sweeping history from 1893 to today. From the fights for public health and immigrants' rights that fueled its founding, to advocating for relief during the Great Depression, all the way to tackling homelessness and AIDS in the 1980s, and into today-Henry Street has been a champion for social justice. Its powerful narrative illuminates larger stories about poverty, and who is "worthy" of help; immigration and migration, and who is welcomed; human rights, and whose voice is heard. For over 125 years, Henry Street Settlement has survived in a changing city and nation because of its ability to change with the times; because of the ingenuity of its guiding principle--that by bridging divides of class, culture, and race we could create a more equitable world; and because of the persistence of poverty, racism, and income disparity that it has pledged to confront. This makes the story of Henry Street as relevant today as it was more than a century ago. The House on Henry Street is not just about the challenges of overcoming hardship, but about the best possibilities of urban life and the hope and ambition it takes to achieve them."--